Isolation, Identification and Risk Factors of Staphylococcus aureus Bacteria in Dairy Goat Milk with Subclinical Mastitis in Siliragung District, Banyuwangi Regency - Faizah, Ayu Nur; Setiawan, Boedi; Saputro, Amung Logam; Warsito, Sunaryo Hadi; Praja, Ratih Novita; Fikri, Faisal (Universitas Airlangga, 2023)
Mastitis is an inflammation of the mammary glands that can cause a sharp reduction in milk production and income for farmers. Subclinical mastitis is mastitis without clinical symptoms but can result in a decrease in the quantity and quality of milk production. One of the main pathogens that cause mastitis namely Staphyloccocus aureus. S. aureus become the biggest problem of mastitis because the cure rate is classified as very low. The risk factors for the occurrence of mastitis, both clinical and subclinical mastitis, can cause a decrease in milk production caused by several factors, including genetic, feed and environmental factors. This study aims to determine the presence of subclinical mastitis in milk of dairy goats with sufferers in Siliragung District, Banyuwangi Regency. Sample testing was carried out at the SIKIA Instrument Laboratory, Airlangga University. Isolation was carried out using MSA (Mannitol Salt Agar) media for further identification consisting of Gram staining and biochemical tests. Some of the biochemical tests used are the catalase test, the coagulase test and the VP test. The results of isolation, observation of characteristics and identification of bacteria in the research that has been carried out show that 64.51% (40/62) of the samples examined were positively identified S. aureus. Results showed that the risk factors for causing subclinical mastitis included cleaning the cage, the number of lactating goats, washing hands before milking, manure and waste management, weaning age and lactation age.